2012
DOI: 10.1001/jama.2012.5588
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Telephone-Administered vs Face-to-face Cognitive Behavioral Therapy on Adherence to Therapy and Depression Outcomes Among Primary Care Patients

Abstract: EPRESSION IS COMMON, WITHthe 1-year prevalence rate of major depressive disorder estimated at between 6.6% and 10.3% in the general population 1,2 and roughly 25% of all primary care visits involving patients with clinically significant levels of depression. 3 Psychotherapy is effective at treating depression, 4 and most primary care patients prefer psychotherapy to antidepressant medication. 5 When referred for psychotherapy, however, only a small percentage of patients follow through. 6 Attrition from psycho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
274
2
18

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 302 publications
(308 citation statements)
references
References 38 publications
14
274
2
18
Order By: Relevance
“…A skilled therapist will be able to deal with such comorbidity and formulate more long-lasting beliefs that, according to cognitive theory, underpin the longer-term risk of depression. Other modes of delivering CBT over the internet 109 or by telephone 118 could retain such a flexible approach, but may also afford an opportunity for greater efficiency in the provision of such treatment.…”
Section: Implications For Health Care and Suggestions For Further Resmentioning
confidence: 99%
“…A skilled therapist will be able to deal with such comorbidity and formulate more long-lasting beliefs that, according to cognitive theory, underpin the longer-term risk of depression. Other modes of delivering CBT over the internet 109 or by telephone 118 could retain such a flexible approach, but may also afford an opportunity for greater efficiency in the provision of such treatment.…”
Section: Implications For Health Care and Suggestions For Further Resmentioning
confidence: 99%
“…There is some evidence to suggest that telephonic consultations can achieve better compliance to treatment as compared to face-to-face consultations [24]. Telephonic consultations can be a preferable method of contact both for patients who do not live close to the pharmacy and for pharmacists as it can allow them to conduct consultations at less busy times [25].…”
Section: Discussionmentioning
confidence: 99%
“…This study highlights that there is a specific effect of telephone-administered CBT that goes beyond the nonspecific effects of a supportive telephone-based intervention. In a more recent study it has been examined how tCBT performs as compared to face-to-face CBT with respect to attrition and symptom reduction [86]. Thereby, it has been shown that while both treatments were associated with a significant symptom reduction posttreatment, with CBT not being noteworthy superior to tCBT, more patients completed tCBT as compared to traditional CBT.…”
Section: New Developments In the Cbt For Depressionmentioning
confidence: 99%